Views on mental health recovery in primary and community mental healthcare services in Thailand: A qualitative study - Natthapon Inta; Annmarie Grealish; Mary Leamy (PLoS ONE, 2026)
Introduction Strong community-based services and healthcare providers with a clear understanding and positive attitudes towards recovery, are central to delivering good quality mental health care in collaboration with service users. Although recovery has been explored in several Asian contexts, its interpretation remains diverse, and consensus on the definition and meaning of personal recovery in Thailand is limited. Further research is needed to explore how mental health service users, carers, and healthcare professionals understand and experience recovery and recovery support, in order to advance recovery-oriented practice within the local sociocultural context. Aim To explore thoughts, perceptions, and experiences of mental health service users, carers, and healthcare professionals on mental health recovery and recovery support in Thailand. Methods A qualitative descriptive study using reflexive thematic analysis, which forms the experience gathering phase of an Experience Based Co-Design (EBCD) study. Thirty semi-structured interviews and two feedback workshops with three service users and eight healthcare professionals were conducted. Results Four themes were identified: (i) conceptions of mental health recovery, (ii) attitudes towards recovery, (iii) characteristics of a successful recovery journey, and (iv) factors impeding recovery. Participants viewed recovery as beginning with clinical and functional improvement, progressing to personal recovery characterised by hope, meaning, and social connectedness. Family support, community acceptance, and supportive healthcare relationships were central to recovery, while barriers operated at individual, family, service, and community levels. Conclusion This study integrates the perspectives of mental health service users, carers, and healthcare professionals to generate new insights into personal recovery within Thai community mental health care. From these findings, we propose a culturally situated Recovery Support Model that foregrounds the interconnected roles of personal agency, family involvement, professional engagement, and community support as drivers of recovery-oriented practice within the Thai mental health system.